2019
DOI: 10.1186/s40854-019-0159-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of risk management strategies on the credit risk faced by commercial banks of Balochistan

Abstract: This study aims to identify risk management strategies undertaken by the commercial banks of Balochistan, Pakistan, to mitigate or eliminate credit risk. The findings of the study are significant as commercial banks will understand the effectiveness of various risk management strategies and may apply them for minimizing credit risk. This explanatory study analyses the opinions of the employees of selected commercial banks about which strategies are useful for mitigating credit risk. Quantitative data was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…In condition 2, the analysis records negative and significant beta coefficients across CAR and ORW, which is not verified for credit risk management. As a matter of fact, this result partially validates H2, and confirms the findings in the previous empirical research stating that innovation influences risk management (Philippas & Siriopoulos, 2009;Mabrouk et al, 2016;Zia et al, 2019).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In condition 2, the analysis records negative and significant beta coefficients across CAR and ORW, which is not verified for credit risk management. As a matter of fact, this result partially validates H2, and confirms the findings in the previous empirical research stating that innovation influences risk management (Philippas & Siriopoulos, 2009;Mabrouk et al, 2016;Zia et al, 2019).…”
Section: Resultssupporting
confidence: 89%
“…González et al (2016) add that securitization increases the overall default risk of European financial institutions. The results for study of Zia, Muhammad, Sarwar and Asif Raz (2019) identified four areas of impact on credit risk management: corporate governance exerts the greatest impact, followed by diversification or innovation, which plays a significant role, hedging and, finally, the bank's Capital Adequacy Ratio. This study highlights these four risk management strategies, which are critical for commercial banks to resolve their credit risk.…”
Section: Financial Innovation and Risk Managementmentioning
confidence: 99%
“…According to Rehman (2019), corporate governance has the greatest impact on credit risk management (CRM), followed by diversification, hedging, and, finally, the bank's Capital Adequacy Ratio. The relevance of these four risk management approaches for commercial banks in addressing credit risk is emphasized in this study.…”
Section: Journal Of Entrepreneurship Management and Innovation Volume...mentioning
confidence: 99%
“…Arora (2014) presented a major difference between government and private banks in India in measuring credit risk. Rehman et al (2019) examined the risk management strategies adopted by commercial banks of Pakistan and found that corporate governance, hedging, diversification, and the banks' capital adequacy ratio, are factors significantly explaining credit risk management. Sirus et al (2019), study suggest that the identification of credit risk significantly affects the credit risk performance.…”
Section: Literature Reviewmentioning
confidence: 99%